Reação farmacodérmica decorrente do uso do levamisol: relato de caso - Sousa, M. G. [UNESP]; Talieri, I. C. [UNESP]; Jorge, A. T. B. [UNESP]; Costa, M. T. [UNESP] (Universidade Federal de Minas Gerais (UFMG), Escola de Veterinária, 2005)
Relata-se a ocorrência de um caso de farmacodermia pelo levamisol e discute-se sobre a manifestação clínica e o estabelecimento do diagnóstico dessa reação cutânea adversa. O animal desenvolveu lesões exsudativas na face, com resolução espontânea após a suspensão do fármaco.

This paper reports the occurrence of a case of pharmacodermic adverse reaction due to levamisole, and provides a discussion about its clinical manifestation and the establishment of the diagnosis of this cutaneous side effect. After receiving levamisole, exsudative lesions developed on the animal's face and recovered spontaneously after this drug was discontinued.
Pharmacodermic adverse reaction due to levamisole: a case report
Keywords: cão; levamisol; farmacodermia; dog; levamisole; pharmacodermic reaction